THE LEVEL OF LIFE QUALITY IN THE WORK OF NURSING TECHNICIANS OF ICU SECTOR IN A UNIVERSITY HOSPITAL FROM NATAL / RN. (Fiep Bulletin - online, 2013)
The concern with the integration of technological, economic and social dimensions and the implications in the health sector with developments on the health of population, has been the object of study in a view of knowledge and practice transformation (MEDEIROS, 2000). In Brazil, interest in the topic Life Quality can be considered recent and there are still doubts about the exact meaning of the term (VERAS, 2003). Objectives: To analyze the level of Life Quality at Work (LQW), in terms of nursing technicians in an Intensive Care Unit (ICU) of a university hospital. Methodology: Descriptive investigation with quantitative approach about conceptions of LQW of the instrument which was applied by means of literature research and questioning, following a simplified model of teacher Marcos Vinicius Carvalho Rodrigues, whose effectiveness had been proven before. Results: We found levels of LQW, by calculating the average percentage of variables for each interviewee, with a range between 35.23% and 86.19%. Then calculated the arithmetic average of the interviewees' individual average, reached to an overall average in percentage terms that represents the technicians level of life quality at work, Nqvt = 58.31%. This result shows that, in view of the interviewees, is somewhat satisfactory, because it's beyond the mark of 50%. In analyzing the responses, it appears that levels of satisfaction are higher on items relating to individual issues, but the decline in organizational issues shows that the line between personal and organizational goals are divergent. Conclusion: The issue of quality in organizations is of relevant importance regarding the achievement of organizational objectives and, specifically, the LQW is a decisive factor in achieving these goals, taking into account the increasing importance of human performance, with its peculiarities, to produce the results expected by the organizations.
Keywords: LQW; Nursing technician; ICU